Análise das Normas Regulamentadoras 18 e 24 do Ministério do Trabalho nas áreas de vivência de canteiros de obras públicas - Queiroz, Humberto Coelho (2018)
Civil construction, in spite of having a positive side of being essential for the country’s development, due mainly to its high level of employability, has also a more obscure one, characterized by a high rate of work accidents. Therefore, some Regulatory Norms (NR) of the Ministry of Labor are directly related to working conditions in the construction industry, such as NR 18 and NR 24, which normalize, for instance, the matter of the welfare facilities within constructions sites, so as to ensure good working conditions in this kind of environment and thereby reduce its number of accidents. Hence, this work aimed at analyzing the application of the Regulatory Norms 18 and 24 in the welfare facilities for public institutions construction sites, raising eventual fines for nonconformities in these constructions, and proposing an integrated management system of these Norms. For that, a checklist based on NR 19 and another on NR 24 were used to raise the nonconformities within each construction analyzed. After applying the checklist in the seven works studied, eventual fines resulting from non-compliance with the Norms were calculated, and, at the end, a way of integrating these two Norms was proposed. The results showed that the seven works presented a large number of nonconformities but, also, the conditions required for implementing an integrated management system for the referred Norms.